Folic acid targeted Mn:ZnS quantum dots for theranostic applications of cancer cell imaging and therapy - Bwatanglang, Ibrahim Birma; Mohammad, Faruq; Yusof, Nor Azah; Abdullah, Jaafar; Hussein, Mohd Zobir; Mohammed Alitheen, Noorjahan Banu; Abu, Nadiah (Dove Medical Press, 2016)
In this study, we synthesized a multifunctional nanoparticulate system with specific targeting, imaging, and drug delivering functionalities by following a three-step protocol that operates at room temperature and solely in aqueous media. The synthesis involves the encapsulation of luminescent Mn:ZnS quantum dots (QDs) with chitosan not only as a stabilizer in biological environment, but also to further provide active binding sites for the conjugation of other biomolecules. Folic acid was incorporated as targeting agent for the specific targeting of the nanocarrier toward the cells overexpressing folate receptors. Thus, the formed composite emits orange–red fluorescence around 600 nm and investigated to the highest intensity at Mn2+ doping concentration of 15 at.% and relatively more stable at low acidic and low alkaline pH levels. The structural characteristics and optical properties were thoroughly analyzed by using Fourier transform infrared, X-ray diffraction, dynamic light scattering, ultraviolet-visible, and fluorescence spectroscopy. Further characterization was conducted using thermogravimetric analysis, high-resolution transmission electron microscopy, field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray fluorescence, and X-ray photoelectron spectroscopy. The cell viability and proliferation studies by means of MTT assay have demonstrated that the as-synthesized composites do not exhibit any toxicity toward the human breast cell line MCF-10 (noncancer) and the breast cancer cell lines (MCF-7 and MDA-MB-231) up to a 500 µg/mL concentration. The cellular uptake of the nanocomposites was assayed by confocal laser scanning microscope by taking advantage of the conjugated Mn:ZnS QDs as fluorescence makers. The result showed that the functionalization of the chitosan-encapsulated QDs with folic acid enhanced the internalization and binding affinity of the nanocarrier toward folate receptor-overexpressed cells. Therefore, we hypothesized that due to the nontoxic nature of the composite, the as-synthesized nanoparticulate system can be used as a promising candidate for theranostic applications, especially for a simultaneous targeted drug delivery and cellular imaging.